Cobras in peril: Reporting the death of two monocled cobra (Naja kaouthia) (Squamata: Elapidae) due to consumption of anthropogenic plastic debris - Ardhendu Das Mahapatra; Vishal Santra; Sunirmal Jana; Sudipta Kumar Ghorai (Journal of Asia-Pacific Biodiversity, 2023)
The impacts of commonly used and often carelessly discarded plastics are well reported in marine animals but have been poorly reported in the terrestrial animals. Here, we report for the first time two cases of dead N. kaouthia from two different habitat types due to consumption of plastic bag and fishing net. We performed a postmortem and recorded observations for both cases, confirmed the cause of death as plastic ingestion and briefly describe the clinical signs and how plastic consumption causes death in N. kaouthia. Here, we highlight how improper waste management impacts each individual's health and sometimes causes painful death in snakes. Our observation indicates that plastic ingestion in snakes is an underestimated cause of death that occurs where the snake's foraging habitat is polluted. We recommend creating awareness, proper waste management, and use of biodegradable/reusable bags can avoid wildlife mortalities in non-protected areas.